Characterising hydrogen micromix flames: combustion model calibration and evaluation - López-Juárez, Marcos; Sun, Xiaoxiao; Sethi, Vishal; Gauthier, Pierre Q.; Abbott, David (American Society of Mechanical Engineers (ASME), 2021)
Hydrogen micromix combustion is a promising concept to reduce the environmental impact of both aero and land-based gas turbines by delivering carbon-free and ultra-low-NOx combustion without the risk of autoignition or flashback. The ENABLEH2 project aims to demonstrate the feasibility of such a switch to hydrogen for civil aviation, within which the micromix combustion, as a key enabling technology, will be matured to TRL3. The micromix combustor comprises thousands of small diffusion flames for which air and fuel are mixed in a cross-flow pattern. This technology is based on the idea of minimizing the scale of mixing to maximize mixing intensity. The high-reactivity and wide flammability limits of hydrogen in a micromix combustor can produce short and low-temperature small diffusion flames in lean overall equivalence ratios. For hydrogen-air mixtures there is a need to further characterise the physical importance and calibration process of the laminar Schmidt (Sc), Lewis (Le) and Prandtl (Pr) and turbulent Schmidt (Sc) numbers. In addition, there is limited numerical and experimental data about flame characteristics and emissions of hydrogen micromix combustor at high pressure and temperature conditions. In this paper, the CFD software STAR-CCM+ was used with the FGM (Kinetic Rate) combustion model to simulate and calibrate hydrogen micromix flames. The research was divided into two parts. In the first part, the values of laminar Schmidt, Lewis and Prandtl numbers for H2 and air, non-reactive, flow mixtures were estimated as 0.22, 0.3 and 0.75 from correlations obtained in the literature. The typical Borghi diagram has been modified to represent this type of diffusion flame, since the assumption of Sc = Le = Pr = 1 can not be applied to hydrogen micromix flames and it is only for premixed flames. This diagram characterizes flame regime based on Damköhler (Da), Karlovitz (Ka) and turbulent Reynolds (Ret) numbers that were calculated from preliminary CFD simulations. In the second part, the value of laminar Schmidt number was set as constant while laminar Lewis and Prandtl numbers were obtained from the flamelet tables. A Turbulent Schmidt number was then obtained by comparing RANS and LES simulations of a single injector. If Sct > 0.2, the predicted NOx production of RANS simulations approaches that of LES; while Sct < 0.2 provides similar overall flame structure between RANS and LES. It is concluded that, for the current simulations, Sct = 0.2 is a good compromise between flame structure and emissions prediction. Flame characteristics and NOx emissions given by Thickened Flame and FGM Kinetic Rate models in a single injector geometry were also compared.
Keywords: hydrogen; micromix; combustion; calibration; ENABLEH2; STAR-CCM+; FGM kinetic rate; thickened flame